"Martin Luther King Fixed It": Children Making Sense of Racial Identity in a Colorblind Society. Issue 5 (5th July 2021) - Rogers, Leoandra Onnie; Moffitt, Ursula; Foo, Christina
Abstract : Children in the United States grow up in a context wherein colorblindness and racism coexist. This article examined how colorblindness functions as a societal "master narrative" that shapes how children construct their own racial identities. Data were collected via semi‐structured interviews with 217 Black, White, and Multiracial children ( M age  = 9.92) in public schools in the Pacific Northwest during 2013–2014 academic year. Our analysis identified four race narratives, which varied systematically by child age and race. Associations were also found between narrative types and children's ratings of racial identity importance. Although colorblindness infuses many of the racial narratives, there was evidence that children also question and disrupt this master narrative with stories of resistance that counter colorblind norms.